If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2(3x + -1) = -2(2x + -7) + 4x Reorder the terms: 6 + 2(-1 + 3x) = -2(2x + -7) + 4x 6 + (-1 * 2 + 3x * 2) = -2(2x + -7) + 4x 6 + (-2 + 6x) = -2(2x + -7) + 4x Combine like terms: 6 + -2 = 4 4 + 6x = -2(2x + -7) + 4x Reorder the terms: 4 + 6x = -2(-7 + 2x) + 4x 4 + 6x = (-7 * -2 + 2x * -2) + 4x 4 + 6x = (14 + -4x) + 4x Combine like terms: -4x + 4x = 0 4 + 6x = 14 + 0 4 + 6x = 14 Solving 4 + 6x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6x = 14 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 14 + -4 6x = 14 + -4 Combine like terms: 14 + -4 = 10 6x = 10 Divide each side by '6'. x = 1.666666667 Simplifying x = 1.666666667
| -7=-5p+6+6p | | 18=-d+11 | | -5x+31x-54=0 | | -3(-5v+8)-v=4(v-9)-4 | | 3x=3/4s | | 8x+y=1 | | x=-585/2 | | 5m-2n=10 | | 8x^2+8X-96= | | 3x+8=-1x+4 | | 5m-2n=10forn | | 2x/9=-65 | | 3x^2+12x+86=0 | | 10000x-2x+4/2x | | 0=4x^2+144 | | 5z+2z-6= | | (3x-7)/-1=y | | -16=8x/5 | | z+13=2 | | v-2300=-800 | | 4(8+y)= | | (a)+(3/a)-(a+4)/(a+5)=(15)/(A^2+5a) | | (1+2v)*5= | | -3(2+5d)=1-5(3d-1) | | 12.6x-3.5x=-273 | | 4x^2+4x-80= | | 17/25+4/5+49/50 | | (X^2-4x)(2x+2)=0 | | 12.6x-3.5=-273 | | 4x-3y=48 | | y=(7-x)/3 | | x+(1/4)x=30 |